The effect of corporate social responsibility activities on customer satisfaction towards hypermarkets in Kuala Lumpur Malaysia - Kadhim, Kadhim Ghaffar; Harun, Amran; Othman, Bestoon Abdulmaged; Falah, Falah Saleem; Alfarttoosi, Ali (Science & Engineering Research Support Society (SERSC), 2020)
This study focused on identifying the effect of activities related to corporate social responsibility on customer satisfaction towards hypermarket. In this study, corporate social responsibility activities were investigated based on four dimensions including, community support, environmentally friendly, sell locally produced products, treating employees. The use of a survey was employed, in which questionnaires were distributed to the respondents, which were 384 customers of selected hypermarkets located within the area of kuala lumpur. An analysis of the collected data was performed using SmartPLS. Based on the result of the statistical analysis, corporate social responsibility activities (community support, environmentally friendly, sell locally produced products, treating employees). This aspect has a desirable consequence on the satisfaction of customers. A conclusion of the study was drawn and a number of recommendations were given based on the findings. One of the major conclusions of the study is that corporate social responsibility activities can only yield optimal performance and customer satisfaction if it is combined with knowledge, experiences and outstanding abilities in the use of community support, environmentally friendly, sell locally produced products, treating employees.